First things first: Mapping the extent of urban agriculture - Dongus, Stefan (Technical Centre for Agricultural and Rural Cooperation, 2006)
Despite the amount of research on urban agriculture, very little is actually known about the extent of farming activities in many cities. Before municipalities can begin to develop institutional support for urban agriculture, they need to know exactly what is going on, and where. That's where GIS comes in.